2007
DOI: 10.1080/10428190701534374
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy followed by autologous stem cell transplantation for relapsed or refractory Hodgkin lymphoma: Prognostic features and outcomes

Abstract: Between January 1990 and April 2001, 115 patients received high-dose chemotherapy (HDT) followed by autologous stem cell transplantation (ASCT) for relapsed or refractory Hodgkin lymphoma (HL). With a median follow-up of 58 months (range, 1 - 175 months), 5-year progression-free survival (PFS) and overall survival (OS) were 46% and 58%, respectively. Twelve patients with primary refractory disease had a 5-year PFS of 41% and OS of 58%, not significantly different from those of the remaining cohort. Early and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…This is consistent with some previously published studies [1519], although this was not shown in the study published by Engelhardt et al [21]. In our study there was a trend towards improvement in RFS in patients who received two lines of chemotherapy in comparison to those who received more than two lines, but this was not statistically significant, probably due to the small sample size.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with some previously published studies [1519], although this was not shown in the study published by Engelhardt et al [21]. In our study there was a trend towards improvement in RFS in patients who received two lines of chemotherapy in comparison to those who received more than two lines, but this was not statistically significant, probably due to the small sample size.…”
Section: Discussionsupporting
confidence: 91%
“…The disease status at the time of transplant (CR versus RD) did not affect the OS or RFS, and this is consistent with Engelhardt et al study [21], but contradicting other studies [14, 17, 20]. We believe that the main reason for this is the small sample size in our study, as there was a trend towards improvement in patients who were in CR over those who had RD, with P values of 0.10 and 0.15 for RFS and OS, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the studies reported, we have included risk factors that were associated with inferior outcome in at least 2 studies. The following adverse factors were identified as useful at time of relapse: anemia (hemoglobin < 10 g/dL), stage (III/IV), remission duration < 12 months, B symptoms, extranodal sites of disease, and bulky disease at diagnosis [20][21][22]24,25,31,40,41,59,61,62,64,81,[134][135][136][137][138][139][140][141][142]. Short remission duration is the factor most consistent across different series.…”
Section: Prognostic Factors For Asctmentioning
confidence: 99%